Nina Grønnum’s model of Danish intonation from an autosegmental-metrical perspective - Bakalova , Maria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
The purpose of this article is to present an overview of Nina Grønnum’s model of Danish intonation and discuss its central assumptions from the perspective of the autosegmental-metrical (AM) theory of intonational phonology. An attempt is made to outline key differences between Grønnum’s model and AM models, as well as summarize the findings from recent empirical investigations of intonation in Danish spontaneous speech and discuss their implications for phonological modeling. Based on that, the article argues that AM theory is not incompatible with the data for Danish intonation (as has been previously claimed by Grønnum). Rather, it is hypothesized that an AM model for Danish would be able to provide a more accurate account of melodic variation in Danish spontaneous speech.